Melestarikan Budaya Pencak Silat Indonesia Melalui Organisasi Persaudaraan Setia Hati Terate (PSHT) - Prayoga, Prayoga (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2025)
This research aims to explore the role of the Persaudaraan Setia Hati Terate (PSHT) organization in preserving Pencak Silat culture in Indonesia. Pencak Silat is a traditional martial art rich in cultural values and philosophy, which has become an integral part of the nation's identity. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews and literature studies. Interviews were conducted with PSHT members, trainers and administrators to gain insight into the exsercises, teachings and activities carried out in the context of preserving Pencak Silat. The research results show that PSHT not only focuses on teaching self-defense techniques, but also instills important moral and ethical values for its members, such as brotherhood, discipline and social responsibility. Apart from that, PSHT is active in organizing various activities, such as regular training, art performances and competitions, which contribute to the sustainability and introduction of Pencak Silat in society. This research also identifies the challenges PSHT faces in cultural preservation efforts, including the influence of modernization and the younger generation's lack of interest in traditional martial arts. As such, support for organizations like PSHT is essential to ensure that this cultural heritage remains alive and relevant among the younger generation. It is hoped that this research can provide a deeper understanding of PSHT's contribution in maintaining and preserving Pencak Silat as part of Indonesia's cultural heritage, as well as inspiring the younger generation to get involved in Pencak Silat activities and appreciate the cultural values contained in it.